Creatine supplementation beyond skeletal muscles: cognitive and neuroprotective effects and underlying mechanisms – a narrative review - Mińkowski, Mikołaj; Oćwieja , Zuzanna; Wyborska , Agata; Fengler, Karolina; Jakubowska , Olga; Kominiak , Dominika; Gascon Carreno , Marcel; Solecka , Katarzyna; Urbanik , Agata; Pietrzak , Kamila (Quality in Sport, 2026)
AIM: The aim of this narrative review was to gather and evaluate current evidence on the effects of creatine supplementation on cognitive function and brain health, with emphasis on mechanisms related to energy metabolism and potential neuroprotective properties. MATERIALS AND METHODS: A narrative literature review was conducted using PubMed and Google Scholar, including randomized controlled trials, systematic reviews, and meta-analyses. The analysis focused on cognitive aspects such as memory, attention, and processing speed, as well as studies examining brain creatine metabolism, especially under conditions of increased metabolic demand. RESULTS: Overall, the evidence suggests that creatine has small but fairly consistent effects on cognitive performance, mainly in short-term and working memory. Regarding attention and processing speed, current evidence suggests that although individual studies show varying degrees of effect, creatine supplementation does not have a significant positive impact on attention and processing speed. The benefits appear more noticeable in situations where the brain is under metabolic stress, such as sleep deprivation, mental fatigue, hypoxia, aging, or low baseline creatine levels. These effects are most likely linked to improved ATP availability, enhanced phosphocreatine buffering, and support of mitochondrial function. CONCLUSIONS: Creatine may offer modest, context-dependent support for cognitive function, particularly when brain energy metabolism is challenged. While effects in healthy individuals seem limited, it may still be a safe and potentially useful option in specific populations. Further research is needed to better define its role and optimal use.